Short‐term neuropsychiatric outcomes and quality of life in COVID‐19 survivors. (13th March 2021) - Méndez, R.; Balanzá‐Martínez, V.; Luperdi, S.C.; Estrada, I.; Latorre, A.; González‐Jiménez, P.; Feced, L.; Bouzas, L.; Yépez, K.; Ferrando, A.; Hervás, D.; Zaldívar, E.; et al.
Abstract: Background: The general medical impacts of coronavirus (COVID‐19) are increasingly appreciated. However, its impact on neurocognitive, psychiatric health and quality of life (QoL) in survivors after the acute phase is poorly understood. We aimed to evaluate neurocognitive function, psychiatric symptoms and QoL in COVID‐19 survivors shortly after hospital discharge. Methods: This was a cross‐sectional analysis of a prospective study of hospitalized COVID‐19 survivors followed up for 2 months after discharge. A battery of standardized instruments evaluating neurocognitive function, psychiatric morbidity and QoL (mental and physical components) was administered by telephone. Results: Of the 229 screened patients, 179 were included in the final analysis. Amongst survivors, the prevalence of moderately impaired immediate verbal memory and learning was 38%, delayed verbal memory (11.8%), verbal fluency (34.6%) and working memory (executive function) (6.1%), respectively. Moreover, 58.7% of patients had neurocognitive impairment in at least one function. Rates of positive screening for anxiety, depression and post‐traumatic stress disorder were 29.6%, 26.8% and 25.1%, respectively. In addition, 39.1% of the patients had psychiatric morbidity. Low QoL for physical and mental components was detected in 44.1% and 39.1% of patients respectively. Delirium and psychiatric morbidity were associated with neurocognitive impairment, and female gender was related with psychiatric morbidity. Conclusion: Hospitalized COVID‐19 survivors showed a considerable prevalence of neurocognitive impairment, psychiatric morbidity and poor QoL in the short term. It is uncertain if these impacts persist over the long term. Abstract :